Assessment of medical and non-medical university students’ knowledge about vitamin D - Wiktoria Ficoń; Renata Polaniak; Beata Całyniuk (Annales Academiae Medicae Silesiensis)
Introduction: Vitamin D is very important for our body. This is confirmed by the World Health Organization (WHO), the Polish Society for Obesity Research (Polskie Towarzystwo Badań nad Otyłością – PTBO) and the Polish Diabetic Society (Polskie Towarzystwo Diabetologiczne – PTD). Nowadays, due to spending most of our time indoors and using sunscreen, we commonly experience deficiencies of this vitamin. In order to assess the knowledge of students from the Medical University of Silesia and the University of Economics in Katowice regarding vitamin D, a survey was conducted based on a proprietary questionnaire available in electronic form. Material and methods: The study was conducted with the help of the author’s questionnaire containing 18 substantive questions. The study involved 272 students. Results: Students of the Medical University of Silesia have a greater knowledge of vitamin D compared to students of the University of Economics in Katowice. A significant number of respondents (49.8%) have an adequate understanding of supplementation, though some are unaware of the recommended standards (34.7%) or the effects of deficiencies (43.6%). Conclusions: Students of the Medical University of Silesia in the vast majority have adequate knowledge related to vitamin D, while the knowledge of students of the non-medical university, namely the University of Economics in Katowice, is lower.